Direct Fiber-Reinforced Composite Onlay for Post-Endodontic Restoration of the Maxillary First Pre-molar - Regina Meilin Syahputri; Noor Hafida Widyastuti; Cahyani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Pulp necrosis is a pathological condition of the dental pulp that requires root canal treatment. Post-endodontic restoration is required to support the success of the root canal treatment, restore dental function, and improve aesthetics. In this case, the final restoration employed was a direct composite onlay with fiber reinforcement. Case: A 30-year-old female patient presented to the Dental Hospital of Soelastri, Universitas Muhammadiyah Surakarta (UMS), with a chief complaint of a carious tooth on the upper right jaw, which had been present for the past year. The diagnosis was established based on subjective, objective, and supplementary examinations. The diagnosis was pulp necrosis with apical periodontitis in tooth 14. Case Management: The patient underwent root canal treatment in accordance with the principles of the endodontic triad. Subsequently, the final restoration was placed as a direct composite onlay with fiber reinforcement. Discussion: A direct composite onlay with fiber reinforcement is a restoration that can be utilized following root canal treatment. The advantages of this restoration include its resistance to masticatory forces, favorable aesthetics, and color resemblance to dentin. Conclusion and Suggestions: Restoration after root canal treatment is crucial to ensure the success of the endodontic therapy. The use of a direct composite onlay with fiber reinforcement represents one of the options for the final restoration following root canal treatment.